Oscillation theorems for the Dirac operator with a spectral parameter in the boundary condition - Ziyatkhan Aliyev; Parvana Manafova (Electronic journal of qualitative theory of differential equations, 2016)
We consider the boundary value problem for the one-dimensional Dirac equation with spectral parameter dependent boundary condition. We give location of the eigenvalues on the real axis, study the oscillation properties of eigenvector-functions and obtain the asymptotic behavior of the eigenvalues and eigenvector-functions of this problem.